2015
DOI: 10.1007/s11892-015-0608-3
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Self-Management Interventions for Adults with Type 2 Diabetes Living in Rural Areas: A Systematic Literature Review

Abstract: In rural communities, high rates of diabetes and its complications are compounded by limited access to health care and scarce community resources. We systematically reviewed the evidence for the impact of diabetes self-management education interventions designed for patients living in rural areas on glycemic control and other diabetes outcomes. Fifteen studies met inclusion criteria. Ten were randomized controlled trials. Intervention strategies included in-person diabetes (n=9) and telehealth (n=6) interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 32 publications
3
58
0
Order By: Relevance
“…For example, they must include tasks around medical or diet adherence (medical self-management), tasks in changing or maintaining new behavioral/life roles within social relationships (role management), or tasks in coping with the emotional burden of living with a long-term condition (emotional management) [42]. To our knowledge, existing reviews mostly focus on medical management [43]. For instance, a recent review that explored online self-management interventions around lifestyle modification examined outcomes that were behavioral (role) and physiological (medical), excluding psychological and emotional management [44].…”
Section: Introductionmentioning
confidence: 99%
“…For example, they must include tasks around medical or diet adherence (medical self-management), tasks in changing or maintaining new behavioral/life roles within social relationships (role management), or tasks in coping with the emotional burden of living with a long-term condition (emotional management) [42]. To our knowledge, existing reviews mostly focus on medical management [43]. For instance, a recent review that explored online self-management interventions around lifestyle modification examined outcomes that were behavioral (role) and physiological (medical), excluding psychological and emotional management [44].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies using CHWs and peer coaches to deliver DSME interventions have found improvements in patient activation levels but did not identify clinically significant improvements in HgA1C levels (Lawson et al, 2013;Lorig, Ritter, Villa, & Armas, 2009;Safford et al, 2015). Although DSME can promote positive health outcomes, education alone may not be sufficient for sustained behavior change (Lepard et al, 2015;Norris, Lau, Smith, Schmid, & Engelgau, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Community-based interventions have been known to improve diabetes outcomes, with most evidence for minority, underresourced, and urban populations; however, increasing evidence is available regarding rural communities (Lepard, Joseph, Agne, & Cherrington, 2015;Palmas et al, 2015). A recent study of rural-dwelling, African-American women found no significant improvements in glycemic control or blood pressure in the community health worker (CHW) intervention group compared to the control group, but significant weight loss (−1.35 ± 6.22 kg) was reported (Lutes, Cummings, Littlewood, Dinatale, & Hambridge, 2017).…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the barriers, the challenges are in adherence to healthy eating, in the practice of physical activity, in glucose monitoring, and in drug therapy (17) . Therefore, this aspect allows for strengthening the participation of health professionals in the development of educational programs, which is an important factor, because studies point to the existence of a direct influence of the total contact time between the user and the educator in terms of optimal program results (4,16,18) . In addition, studies have pointed out, among their key findings, the benefits obtained by educational interventions in the treatment and control of diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%